Coronary Sinus to Left Atrial Communication. (4th August 2009) - Scheller, Vandhana; Mazur, Wojciech; Kong, James; Chung, Eugene S.
Abstract : Congenital coronary sinus anomalies are rare in clinical practice, partly due to the lack of symptoms. We present a case of coronary sinus anomaly causing a right-to-left intracardiac shunt in a 46 years/old African American female with a past medical history of obstructive sleep apnea, diabetes mellitus, hypertension, coronary artery disease, and ischemic cardiomyopathy who presented with hypoxia. In the months prior to her presentation, she had suffered an inferior myocardial infarction with right ventricular involvement, as well as resulting severe tricuspid regurgitation. In conclusion, further investigations revealed a communication between the coronary sinus (CS) and left atrium (LA).